Narrative inquiry : experience and story in qualitative research / D. Jean Clandinin, F. Michael Connelly. - Clandinin, D. Jean (Jossey-Bass, 2000)
In this definitive guide and comprehensive resource, the authors draw from more than 20 years of field experience to show how narrative inquiry can be used in educational and social science research.